Investigating the Guidance Offered to Teachers in Curriculum Materials: The Case of Proof in Mathematics - Stylianides, Gabriel J. (International Journal of Science and Mathematics Education, 2008)
Despite widespread agreement that proof should be central to all students’ mathematical experiences, many students demonstrate poor ability with it. The curriculum can play an important role in enhancing students’ proof capabilities: teachers’ decisions about what to implement in their classrooms, and how to implement it, are mediated through the curriculum materials they use. Yet, little research has focused on how proof is promoted in mathematics curriculum materials and, more specifically, on the guidance that curriculum materials offer to teachers to enact the proof opportunities designed in the curriculum. This paper presents an analytic approach that can be used in the examination of the guidance curriculum materials offer to teachers to implement in their classrooms the proof opportunities designed in the curriculum. Also, it presents findings obtained from application of this approach to an analysis of a popular US reform-based mathematics curriculum. Implications for curriculum design and research are discussed.
Keywords: Curriculum Development; Mathematics Education; Science Education; TEACHERS; curriculum analysis; equivalent expressions; mathematical tasks; mathematics curriculum; proof; textbooks